Activity of Eucalyptus Globulus essential oil in the control of bacteria in the oral cavity (Research, Society and Development, 2021)
Eucalyptus globulus oil has several pharmacological properties. Among them, its antiseptic, expectorant, antifungal and antimicrobial effects stand out. The present work had the general objective of evaluating the activity of Eucalyptus globulus oil in the control of bacteria of the oral cavity and specific objectives to compare the effect of Eucalyptus globulus oil with chlorhexidine effect and to determine in which bacterial strains the oil of Eucalyptus globulus was more effective. The antimicrobial activity was tested in bacteria of the group Escherichia coli (E. coli), Enterococcus faecalis (E. faecalis) and Staphylococcus aureus (S. aureus) by the agar diffusion method with the well technique. The wells were filled with solutions of 0.12% chlorhexidine and Eucalyptus globulus oil in concentrations of 100%, 50%, 25%, 10%, 1% and 0.1% in order to compare the antimicrobial effect by inhibition growth. The tests were performed in triplicate and the statistical analysis was performed using Student's T-test. The data were organized into tables for the demonstration of the results obtained. Values of p